The Impact of Migration and Remittances on Employment in Agriculture in the Gambia - Ebrima K. Ceesay (Journal of Agronomy Research, 2020)
For economic growth and development in any WE African country the GDP progress is depending on the key push-pull factors as migration, personal remittances received, bilateral aids and, absolutely, employment in agriculture which is about 1/3 of the population and not a predominant and protected minority as happens in the industrialized EU and North America. In order to represent the framework of the reciprocal dependencies the present study used the statistics of Gambia from WDI covering the periods from 1960 to 2017 by applying linear regression models. The results confirmed that migration and remittances have significant positive impact on employment in agriculture because new investment in agriculture created new skilled and unskilled employment. The results also found out that employment in agriculture has negative and significant impacts on foreign aids: 10% increase in migration, increases foreign aid by 50.3%. Increasing 10% of remittance, increase economic growth by 0.14% but 10% increases in employment in agriculture, decrease economic growth by 0.04%. To face globalization the economy of the Gambia should use the foreign aid to improve agriculture production and productivity thereby increase economic growth through human capital theory of migration, skilled migration, export and food security, the study recommends.
Keywords: Economic development